Factors in the provision of engaging experiences for the traditionalist market at visitor attractions. (April 2021) - Leask, Anna; Barron, Paul
Abstract: The global population is ageing with implications for the provision of tourism experiences to meet changing needs. The shift in demographics has encouraged a focus on the older visitor with tourism organisations recognising the value of engaging with this market, though little research exists to inform the development of experiences. Many in the 'Traditionalist' category, born pre-WW2, have a lifetime habit of visiting attractions but find it increasingly difficult to continue this engagement. Barriers include available time due to multiple social and caring responsibilities and concerns regarding physical and intellectual accessibility, while attraction managers lack data on this market's needs, leading to misconceptions and limited provision. Key enablers are inclusive design, clear communication of access, and the provision of specifically designed experiences. Key features of these to be regular events to develop visitor familiarisation, and to include interactive activities relating to attraction assets and a strong socialisation aspect. Highlights: The ageing population actively want to engage with visitor attractions. Barriers are availability of time and physical and intellectual accessibility. Economic and social reasons motivate engagement with older visitors. Enable engagement via specifically designed social experiences.